Application of advanced spaceborne thermal emission and reflection radiometer (ASTER) data in geological mapping - Pour, Amin Beiranvand (Academic Journals, 2011)
The spectral and spatial properties of the advanced spaceborne thermal emission and reflection radiometer (ASTER) data can be used in detailed lithological and hydrothermal alteration mapping related to copper and gold mineralization, particularly the shortwave infrared radiation subsystem where hydrothermal alteration minerals have diagnostic spectral absorption features. This paper reviews the technical characteristics of ASTER data and related image processing techniques applicable to ASTER data for lithological and hydrothermal alteration mineral mapping. The hydrothermal alteration zones associated with porphyry copper deposit, such as phyllic, argillic and propylitic, can be discriminated from one another by virtue of their spectral absorption features, which are recognizable by ASTER special bands. The differentiation and identification of phyllic zone are important for exploring porphyry copper mineralization as an indicator of the high potential area with economical mineralization of copper. In this way, we attempt to demonstrate how ASTER remote sensing data can identify and discriminate the hydrothermal alteration zones and lithological units in a regional scale. It is therefore concluded that remote sensing techniques are viable options for geological applications, offering reliable and relatively low cost methods, and could be utilized further to other virgin regions for lithological mapping and for initial steps of mineral exploration.